Analisis Keputusan Pembelian Produk Wardah melalui Celebrity Endorsement dan Kualitas Produk - Riski Apriani; Esti Dwi Rahmawati; Agus Suyatno (Universitas 45 Surabaya, 2024)
The pace of the cosmetics/beauty product industry in Indonesia increases every year. In Indonesia there are several beauty product brands such as: Wardah, Sariayu, MS Glow, Emina, Somethinc, Avoskin, Lacoco, Azarine, PS Glow, Dear Me Beauty, Y.O.U Beauty, Purbasari, Scarlett Whitening, Madame Gie, Make Over. This research aims to analyze celebrity endorsement and product quality on purchasing decisions for Wardah products. The data used is primary and secondary data. The data collection method uses a questionnaire via Google Form. The analysis technique uses the Structural Equation Modeling-Part Least Square (SEM-PLS) method. The sampling technique uses a non-probability technique with purposive sampling type. A sample of 97 respondents was obtained. The data processing technique uses the SmartPLS 4.1 program. The variables in this research are the independent variables, namely celebrity endorsement and product quality, and the dependent variable, namely purchasing decisions. The research results show that celebrity endorsement has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions.